2022
DOI: 10.3803/enm.2021.1293
|View full text |Cite
|
Sign up to set email alerts
|

Dulaglutide Ameliorates Palmitic Acid-Induced Hepatic Steatosis by Activating FAM3A Signaling Pathway

Abstract: Background: Dulaglutide, a long-acting glucagon-like peptide-1 receptor agonist (GLP-1RA), has been shown to reduce body weight and liver fat content in patients with type 2 diabetes. Family with sequence similarity 3 member A (FAM3A) plays a vital role in regulating glucose and lipid metabolism. The aim of this study was to determine the mechanisms by which dulaglutide protects against hepatic steatosis in HepG2 cells treated with palmitic acid (PA). Methods: HepG2 cells were pretreated with 400 μM PA for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… Antidiabetic drugs PPARα agonist Bezafibrate MCD diet-fed male KK-Ay/TaJcl (KK-Ay) mouse model ↓Lipid accumulation ↓Hepatic inflammation ↓Fibrosis ↓Plasma ALT, TG ↑Hepatic fatty acid β-oxidative genes Bezafibrate reduced the mRNA levels of profibrogenic and fibrogenic genes in TGF-β1-stimulated RI-T cells 147 , 149 GW7647 Choline-deficient L-amino acid–defined diet containing 45% fat (HF-CDAA) diet-fed mouse model ↓Liver/BW ratio ↓Serum TG ↓Liver steatosis 148 Gemcabene STAM™ murine model of NASH ↓Hepatic mRNA markers of inflammation, lipogenesis and lipid modulation, fibrosis 150 PPARδ agonist Seladelpar (MBX-8025) Atherogenic diet-fed Alms1 mutant ( foz/foz ) mouse model ↓Hyperglycemia, hyperinsulinemia, and whole-body insulin resistance ↓Blood glucose, ALT ↓Apoptosis ↓Inflammation ↓NAS 151 Antidiabetic drugs GLP agonist Dulaglutide (LY2189265) HFHC diet-fed mouse model ↓Body weight ↓AST, glucose levels ↓Inflammation No effects on NAS Score and liver TG. 606 , 607 GLP-1/GLP-2R dual agonist GLP-1/2-Fc fusion Choline-deficient high-fat diet with high fructose and sucrose water (CDHF-FC)-fed mouse model ↓Body weight, glucose levels, hepatic TG, and cellular apoptosis. ↓Liver fibrosis, insulin sensitivity.…”
Section: Signaling Pathways Driving Nafl/nash Development and Related...mentioning
confidence: 99%
“… Antidiabetic drugs PPARα agonist Bezafibrate MCD diet-fed male KK-Ay/TaJcl (KK-Ay) mouse model ↓Lipid accumulation ↓Hepatic inflammation ↓Fibrosis ↓Plasma ALT, TG ↑Hepatic fatty acid β-oxidative genes Bezafibrate reduced the mRNA levels of profibrogenic and fibrogenic genes in TGF-β1-stimulated RI-T cells 147 , 149 GW7647 Choline-deficient L-amino acid–defined diet containing 45% fat (HF-CDAA) diet-fed mouse model ↓Liver/BW ratio ↓Serum TG ↓Liver steatosis 148 Gemcabene STAM™ murine model of NASH ↓Hepatic mRNA markers of inflammation, lipogenesis and lipid modulation, fibrosis 150 PPARδ agonist Seladelpar (MBX-8025) Atherogenic diet-fed Alms1 mutant ( foz/foz ) mouse model ↓Hyperglycemia, hyperinsulinemia, and whole-body insulin resistance ↓Blood glucose, ALT ↓Apoptosis ↓Inflammation ↓NAS 151 Antidiabetic drugs GLP agonist Dulaglutide (LY2189265) HFHC diet-fed mouse model ↓Body weight ↓AST, glucose levels ↓Inflammation No effects on NAS Score and liver TG. 606 , 607 GLP-1/GLP-2R dual agonist GLP-1/2-Fc fusion Choline-deficient high-fat diet with high fructose and sucrose water (CDHF-FC)-fed mouse model ↓Body weight, glucose levels, hepatic TG, and cellular apoptosis. ↓Liver fibrosis, insulin sensitivity.…”
Section: Signaling Pathways Driving Nafl/nash Development and Related...mentioning
confidence: 99%
“…We also found that dulaglutide could decrease hepatic lipid accumulation by activating family with sequence similarity 3 member A (FAM3A) signaling pathway [116]. In this study, dulaglutide demonstrated significant reductions in hepatic lipid accumulation and suppression of genes linked to LD binding proteins, DNL, and TG synthesis in palmitic acid treated HepG2 cells.…”
Section: Experimental Perspective On Nafldmentioning
confidence: 50%
“…In vitro studies, HepG2 cells treated with palmitic acid (PA) were found that dulaglutide significantly reduced liver lipid accumulation and gene expression related to lipid drop-binding proteins, de novo adipogenesis and TG synthesis. And dulaglutide increased the expression of proteins associated with lipolysis and fatty acid oxidation, as well as family with sequence similarity 3 member A (FAM3A) [56]. In the HepG2 fatty liver cell model, hypoxia-inducible factor-2alpha (HIF-2α)/PPARα pathway was found to be essential for Lira to inhibit liver lipid synthesis and reduce lipid-induced hepatic steatosis [57].…”
Section: Glp-1 Modulates Fat Synthesis In the Livermentioning
confidence: 99%